Casualties of preparedness: the Global Health Security Index and COVID-19. Issue 2 (June 2021) - Mahajan, Manjari
Abstract: The 2019 Global Health Security Index (GHS Index) assessed the US and the UK as the two countries best prepared to address a catastrophic pandemic. The preparedness rankings of this index have had little correlation with the actual experiences of COVID-19 in various countries. In explaining this disrepancy, the paper argues that better indicators and more data would not have fixed the problem. Rather, the prevailing paradigm of global health security that informs instruments such as the GHS Index needs to be interrogated. This dominant paradigm narrowly conceptualises global health security in terms of the availability of a technical infrastructure to detect emerging infectious diseases and prevent their contagion, but profoundly undertheorises the broader social and political determinants of public health. The neglect of social and political features is amplified in instruments such as the GHS Index that privilege universalised templates presumed to apply across countries but that prove to be inadequate in assessing how individual societies draw on their unique histories to craft public health responses.